A cross-sectional study to estimate the prevalence of text neck syndrome among medical students in a tertiary care teaching hospital in Andhra Pradesh - Sravya Teja Paleti; Rohit Inuganti; S. V. Gopala Krishna; Rojah Islam (MRIMS Journal of Health Sciences)
Background: The overuse of handheld mobile technology is leading to detrimental effects on the human body, one of which is text neck syndrome (TNS). This refers to neck pain and disability due to repetitive stress injury. Text neck can cause symptoms such as neck pain, shoulder pain, upper back pain, and increased curvature of spine. Objectives: The objective of this study was to estimate the prevalence, awareness, frequency, severity, and radiation of pain experienced by medical students and to determine the association between the duration of gadget usage and the severity of pain. Methodology: In this cross-sectional study, 1000 medical students were surveyed regarding the awareness and prevalence of TNS. The questionnaire consisted of 16 questions which included, demographic details and education details, and questions related to frequency, duration, purpose and time of usage, and position during use. Results: Out of 1000 students, 500 of the respondents did not know of TNS, 10 knew the term in detail, 160 were familiar with the term, and 330 had only heard of the term. The usage of electronic gadgets increased with age and was found statistically significant with P < 0.05. A significant positive association (P < 0.05) was found between the duration of usage of gadgets and the severity of pain. Conclusion: TNS is a real problem, and the students are not aware of the problem. The study showed that the longer the duration of gadget usage, the more adverse the symptoms.